Elektrischer Transport durch Nanokontakte von Selten-Erd-Metallen - Berg, Oliver (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2014)
In this book the electronic transport through rare-earth nanocontacts is investigated. These nanocontacts can be fabricated by the mechanically controlled break-junctions. The conductance through such a nanocontact is strongly influenced by the element's electronic structure. This is probably caused by the variable strength of localization of the 4f states.